Sleep Disturbances and Attention Deficit Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The relationship of sleep disorders, attention deficit hyperactivity disorder (ADHD), comorbidity associated with ADHD, and treatment with stimulant medications was determined using 2 sleep questionnaires completed by the parents in a study of children aged 6 to 12 years treated at the Hospital for Sick Children, Toronto, Canada.